Axially symmetric flow with free boundary - Minenko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove the solvability of a boundary-value problem with the Bernoulli condition in the form of an inequality on a free boundary. By using the Rietz method, we construct an approximate solution that converges to an exact solution in the integral metric.